Data warehouse design on the basis of Hierarchical Degenerate Snowflake (HDS) - Zaker, Morteza; Yasin, Norizan Mohd; Amnuaisuk, Somnuk Phon; Haw, Su Cheng (Inderscience, 2011)
Two of the most data model in Data Warehouse (DW) and advanced database includes star and snowflake schema, which play pivotal roles in the underlying performance. Today, DW queries comprise a group of aggregations and joining operations. As a result, snowflake schema does not seem to be an adequate option since several relations must combine to provide answers for queries that involve aggregation. In spite of its widespread application and undeniable advantages, snowflaking technique has certain theoretical and practical demerits. This paper proposes Hierarchical Degenerate Snowflake (HDS) as an alternative logical data model to achieve DW structure to improve the query performance. Copyright © 2011 Inderscience Enterprises Ltd.